Gendering addiction: the politics of drug treatment in a neurochemical world - Campbell, Nancy D. (Palgrave Macmillan, 2011)
Getting gender on the agenda: a history of pioneers in drug treatment for women -- Raising consciousness or controlling women? Women's drug and alcohol treatment re-emerges -- Undue burdens: the emergence of feminist treatment advocacy in a masculinist system -- 'Unearthing women' in drug policy: where do women fit-or do they? -- Reproducing bodies and governing motherhood: drug-using women and reproductive loss